Analisis Kelayakan Kebahasaan Buku Ajar Bahasa Arab Kelas III Madrasah Ibtidaiyah Terbitan Grafindo Berdasarkan Standar BSNP - Maftuhin, Ahmad Najib; Fakhruddin, Muhammad Zaky (Department of Arabic Education - Faculty of Educational Sciences, 2024)
This study aims to analyze the linguistic feasibility of the Arabic textbook for Grade III Madrasah Ibtidaiyah published by Grafindo Media Pratama. The analysis was conducted based on linguistic feasibility criteria, which include compatibility with students' developmental levels, grammatical accuracy, clarity of sentence structure, and the use of relevant and easily understandable vocabulary. This research employed a qualitative descriptive approach with data collection techniques consisting of document studies and content analysis. The results indicate that, in general, the textbook meets most of the linguistic feasibility criteria. The language used is relatively simple and suitable for students' abilities, although there are some deficiencies in term consistency and adherence to standard Arabic grammar rules. Therefore, revisions to certain sections are recommended to enhance the linguistic quality of the textbook, making it more effective in supporting Arabic learning at the Madrasah Ibtidaiyah level.